Fixed point theory and applications - Agarwal, Ravi P. (Cambridge tracts in mathematics, 2001)
A clear exposition of the flourishing field of fixed point theory. Most of the main results and techniques are developed, together with applications in analysis. Researchers and graduate students in applicable analysis will find this to be a useful survey of the fundamental principles of the subject.